Surface and redox characterization of new nanostructured ZrO2@CeO2 systems with potential catalytic applications. (17th April 2018) - Barroso‐Bogeat, Adrián; Núñez‐Pérez, Bernardo; Blanco, Ginesa; Pintado, José María; Hernández‐Garrido, Juan Carlos; Calvino, José Juan
Abstract : Ceria‐zirconia mixed oxides are widely used as catalysts and catalytic supports. Nevertheless, due to economic and geo‐strategic concerns, reducing and optimizing the lanthanide content in these formulations while preserving or even improving their excellent redox and catalytic properties has become a challenge for current research. In this context, the design of core@shell nanostructures arises as a feasible alternative to achieve the aforesaid goal. In the present work, a new nanostructured ZrO2 @CeO2 system based on spherical and mesoporous zirconia cores coated by a well‐dispersed nanometer‐thick ceria layer has been prepared by a novel synthetic approach in 2 different steps: (1) synthesis of the zirconia cores by a sol‐gel method and (2) coating with a thin ceria shell by controlled chemical precipitation. The resulting nanocomposite was characterized by several techniques, which clearly reveal its perfect core@shell nanostructure and enhanced reducibility as compared with pure ceria.